The Manuscript Kifayah Al-Muhtaj fi Al-Isra Wa Al-Miʻ'raj By Sheikh Daud Al-Fatani: a Brief Review - Binti Awang Haji Junggal, Amalina; Pg Hj Abd Rahim, Pg Mohd Wafi (Journal of Islamic History and Manuscript, 2025)
The event of Isra’ and Mi'raj is one of the most significant events in Islam. This event holds deep meaning, especially for the Muslim community. Manuscripts have been used as a medium to share the story of Isra’ and Mi'raj. One of the most influential manuscripts in the Nusantara region about Isra’ and Mi'raj is Kifayah al-Muhtaj fi al-Isra wa al-Miʻraj, written by Sheikh Daud al-Fatani, a scholar from Patani and now preserved in the Balai Khazanah Islam Sultan Haji Hassanal Bolkiah. This research uses a philological study. The research results show that Balai Khazanah Islam Sultan Haji Hassanal Bolkiah houses several important Islamic manuscripts, one of which is the Kifayah al-Muhtaj fi al-Isra wa al-Miʻraj manuscript by Syekh Daud al-Fatani. The existence of this manuscript affirms the intellectual development of Islam in the Nusantara region, marked by the production and reproduction of Islamic texts. It also emphasizes that Jawi script, the Arabic letters used in Malay phonology, became one of the distinctive features of Islamic manuscripts produced in the Nusantara region.